(3QSGdI aj HjGf GdeTQhY hZjQ GdeTQhY aj GdUdGIs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf hGdUdGI hGdSdGe Ydi QShdg eMeO hBdg CLeYjf adGHO ef HjGf CfhGY GdeTQhYGJ hZjQ GdeTQhYGJ hHjGf eYGfjgG hCMcGegG djSgd Ydi GdWGdH OQcgG hVHWgG s
(3BNQgG (B:s
(3GdHGH GdKGef (B: (3aj GdeaSOGJ hgj GdJMbjb NeSI Ydi GdYehe (B: (3GdJcde HcdGe GdfGS eWdbG MbjbI Ch MceG hGdVMc hGdYed GdcKjQ HdG GMJjGL hJQc aQV ef GdaQGFV dG YPQ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdabg GdMfHdjs